Altered Mental Status in an Older Adult: A Case-Based Exercise for Medical Students - Gary S. Winzelberg; Amy C. Denham (Association of American Medical Colleges, 2013)
Abstract Introduction This case-based exercise, designed for second-year medical students, covers principles of diagnosis and management of delirium in older adults. It provides a structured team-based setting in which groups of medical students can practice clinical reasoning skills. It has been used as part of a series of clinical cases created to help students synthesize what they have learned in different organ system courses and apply their knowledge to geriatric practice. Methods The case presents an 86-year-old man brought to an emergency room by his son because of lethargy. Learners should progress through the case and work towards a differential diagnosis for a geriatric patient with altered mental status. The facilitator guide includes the objectives for the case, a suggested schedule, ideas for effective implementation, and an answer guide for all of the assignments that students will be working on over the course of the exercise. A separate document contains all of the student materials that should be provided during the exercise. Results A version of this case has been used in our institution for the last four years, with a total of approximately 640 second-year medical students. Although we haven't solicited formal feedback from faculty, our small group facilitators consistently comment that they are impressed by the level of student engagement and the clinical sophistication of students' small-group discussions. Student satisfaction with the exercise has steadily increased over the 4 years that we have run the case. Discussion This case requires preclinical students to integrate and synthesize learning from many different courses and disciplines. In our experience, the modified team-based learning approach that this exercise generates lively and clinically sophisticated discussions among second-year medical students.